Environmental Health Risk Analysis of Exposure Carbon Monoxide (CO) on Traders in Manado City Self-Service Jumbo Area - Daniel Y Sualang; Oksfriani Jufri Sumampouw; Ricky C Sondakh (CV. Science Tech Group, 2026)
Background: Motor vehicle activity in shopping mall areas is a primary source of carbon monoxide (CO) emissions, posing a potential long-term health risk for workers with sustained exposure. This study aimed to conduct an environmental health risk assessment of CO exposure for traders operating in the Jumbo Supermarket Area of Manado City. Methods: An observational study with a quantitative approach was conducted in July-August 2025. Ambient air CO concentration was measured in real-time using a CO meter at three location points, with purposive sampling of 30 traders. Respondent characteristics, including exposure parameters, were collected via questionnaire. Health risk analysis was performed by calculating the Average Daily Dose (ADD) and Risk Quotient (RQ), following the US EPA (2022) guidelines, where an RQ > 1 indicates an unacceptable non-carcinogenic risk. Results: The mean ambient CO concentration was 1,591.89 µg/m³, which is significantly below the national air quality standard (10,000 µg/m³) set by Indonesian Minister of Health Regulation No. 02 of 2023. The risk assessment yielded average RQ values of 8.38 x 10⁻⁵ for real-time exposure and 1.23 x 10⁻⁵ for lifetime exposure. All calculated RQ values were substantially below the safety threshold of 1. Conclusion: Current CO concentrations in the study area do not exceed regulatory standards and do not pose an unacceptable non-carcinogenic health risk to traders. However, implementing periodic air quality monitoring is recommended to ensure the continued protection of worker health in this environment.